Answer:
[tex]f(x)=x^2+36[/tex]
Step-by-step explanation:
We want to find the equation in standard form for a polynomial that has zeros at x=6i and x=-6i.
So, we will have the two factors:
[tex](x-(6i))\text{ and } (x-(-6i))[/tex]
So, our polynomial will be:
[tex]f(x)=(x-6i)(x+6i)[/tex]
Distribute:
[tex]f(x)=x(x+6i)-6i(x+6i)[/tex]
Distribute:
[tex]f(x)=x^2+6xi-6xi-36i^2[/tex]
Combine like terms:
[tex]f(x)=x^2-36i^2[/tex]
Remember that i²=-1. Hence:
[tex]f(x)=x^2-(-36)[/tex]
Simplify. So, our polynomial is:
[tex]f(x)=x^2+36[/tex]